Security Analysis and Portfolio Management: An Analytical Approach to Investment. - Rogoff, Donald L.; Keller, Thomas F. (The Accounting Review, 1972)
Reviews the book "Security Analysis and Portfolio Management: An Analytical Approach to Investments," by Steven E. Bolten.